Brainstorming and Methapor Patterns in Creativity, Insya Hurr, Through Online Learning on Instagram hashtags - Ade Destri Deviana; Lailatul Mubaarokah (Arabic Education Department, Islamic Studies Faculty, Universitas Muhammadiyah Malang, 2021)
Creative thinking is one of the learning objectives proclaimed by the Indonesian government. Creativity includes four aspects, namely flexibility, originality, fluency and elaboration. The purpose of this study was to describe the implementation of these two patterns in learning insya hurr with Instagram hashtags. The research method used was descriptive qualitative of 98 active students (classes A, B, C) in semester II of the Department of Arabic Language Education STIQ Amuntai South Kalimantan for the period 2019-2020. The results of the study were the implementation of learning in 4 stages, namely: (1) the stage of brainstorming on creativity criteria on flexibility and originality by generating new ideas as story titles; (2) the brainstorming stage of fluency and elaboration creativity criteria with developing ideas into stories with the help of 5W1H and pictures; (3) metaphor on connect, relate, explore, and analyze with the review process; (4) metaphor the transform and experience with the publication and appreciation process (verbal and extrinsic motivation). Students could develop ideas that are varied and different from the writings of their peers, have the confidence to publish their own work with a good sentence structure. Students got motivation, support and direction for writing improvements because the lecturer in this pattern was the motivator and reviewer without giving an assessment in the form of numbers and without rejecting student ideas (all ideas are considered to be correct with improvements). In the process of implementing learning, students couldn’t know the results of the achievements in the form of numbers.